Religious Mental Development and Performance of TNI AD Case Study at Kodim 0913/PPU, Penajam Paser Utara Regency, East Kalimantan Province - Sri Muryani; Mega Hidayati; Marsudi Imam (Budapest International Research and Critics University, 2022)
This thesis discusses the issue of Religious Mental Development and Army Performance at the 0913/PPU Kodim, which aims; First, to find out the process of religious mental development carried out at Kodim 0913/PPU in the form of the material provided, the method used and its implementation. Second, to find out the results of mental development on the performance of the Indonesian Army at the Kodim 0913/PPU. This research is qualitative research with the key instrument being the researcher himself. Data collection was obtained through observation, interviews and documentation. Meanwhile, the data analysis was carried out inductively which was more concerned with meaning than generalizing the data using three approaches, namely the military, psychological and normative theological approaches. The data sources for this research consisted of the leadership of Kodim 0913/PPU, staff officers, all soldiers and their families and the surrounding community if needed. The results of this study indicate that the mental development of TNI AD soldiers at Kodim 0913 / PPU is carried out with all the characteristics carried out in the military environment, both in terms of procedures, methods and implementation techniques. The mental training carried out turned out to have a good influence on the performance of the Indonesian Army at the 0913/PPU Kodim. The implementation of mental development at Kodim 0913/PPU has not yet been implemented perfectly, there are still many things that need to be improved, such as the professionalism of mental coaches, methods of mental development and mental development materials. The leadership support and the prevailing military tradition (command system) strongly support the implementation of mental development.